He is the One: The Matrix Trilogy's Postmodern Movie Messiah - Stucky, Mark D. (The journal of religion and film, 2005)
Many films have used Christ figures to enrich their stories. In The Matrix trilogy, however, the Christ figure motif goes beyond superficial plot enhancements and forms the fundamental core of the three-part story. Neo's messianic growth (in self-awareness and power) and his eventual bringing of peace and salvation to humanity form the essential plot of the trilogy. Without the messianic imagery, there could still be a story about the human struggle in the Matrix, of course, but it would be a radically different story than that presented on the screen.